Remembering faces with emotional expressions - Liu, Chang Hong; Chen, Wenfeng; Ward, James (Frontiers in Psychology, 2014)
It is known that happy faces create more robust identity recognition memory than faces with some other expressions. However, this advantage was not verified against all basic expressions. Moreover, no research has assessed whether similar differences also exist among other expressions. To tackle these questions, we compared the effects of six basic emotional expressions on recognition memory using a standard old/new recognition task. The experiment also examined whether exposure to different emotional expressions at training creates variable effects on transfer of the trained faces to a new/neutral expression. Our results suggest that happy faces produced better identity recognition relative to disgusted faces, regardless of whether they were tested in the same image or a new image displaying a neutral expression. None of the other emotional expressions created measurable advantage for recognition memory. Overall, our data lend further support for the happy face advantage for long-term recognition memory. However, our detailed analyses also show that the advantage of happy expression on identity recognition may not be equally discernible from all other emotional expressions.